2017
DOI: 10.1002/pmic.201700034
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Incorporate Multi‐Enzyme Digestion into C‐TAILS for C‐Terminomics Studies

Abstract: Protein C-termini study is still a challenging task and far behind its counterpart, N-termini study. MS based C-terminomics study is often hampered by the low ionization efficiency of C-terminal peptides and the lack of efficient enrichment methods. We previously optimized the C-terminal amine-based isotope labeling of substrates (C-TAILS) method and identified 369 genuine protein C-termini in Escherichia coli. A key limitation of C-TAILS is that the prior protection of amines and carboxylic groups at protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 43 publications
(76 reference statements)
3
30
0
Order By: Relevance
“…It is challenging to biochemically identify the C-terminus of proteins biochemically as the C-terminal is relatively less reactive than the amino terminus (Marino et al 2015). Nevertheless, the TopFIND group improvised MS techniques, such as C-terminal amine-based isotope labeling of substrates (C-TAILS) and combined fractional diagonal chromatography to identify 130,182 neo C-termini (Bonetto et al 1997; Sechi and Chait 2000; Colaert et al 2013; Nika et al 2013; Fortelny et al 2015; Zhang et al 2018). Proteomic analysis of Escherichia coli , Mus musculus , and Homo sapiens identified that >10% of C-termini are derived from proteolysis, thus we estimate that endoproteolysis produces at least 2000 new human C-termini (Lange and Overall 2013).…”
Section: C-termini Backgroundmentioning
confidence: 99%
“…It is challenging to biochemically identify the C-terminus of proteins biochemically as the C-terminal is relatively less reactive than the amino terminus (Marino et al 2015). Nevertheless, the TopFIND group improvised MS techniques, such as C-terminal amine-based isotope labeling of substrates (C-TAILS) and combined fractional diagonal chromatography to identify 130,182 neo C-termini (Bonetto et al 1997; Sechi and Chait 2000; Colaert et al 2013; Nika et al 2013; Fortelny et al 2015; Zhang et al 2018). Proteomic analysis of Escherichia coli , Mus musculus , and Homo sapiens identified that >10% of C-termini are derived from proteolysis, thus we estimate that endoproteolysis produces at least 2000 new human C-termini (Lange and Overall 2013).…”
Section: C-termini Backgroundmentioning
confidence: 99%
“…In efforts to optimize the protocol, modification of protein primary amines by acetylation rather than dimethylation appeared beneficial and inclusion of single charged ions during mass spectrometry analysis increased the number of identified C termini [69]. Furthermore, the first amine protection step may also be omitted without obvious detrimental effect, as the concentration of protein primary amines appeared negligible compared to the excess amidation reagent used for carboxyl modification [70].…”
Section: Global Enrichment Of Protein C-terminal Peptidesmentioning
confidence: 99%
“…This is exacerbated by the fact that C-terminal peptides in tryptic digest lack basic residues and thus are less likely to ionize. The alternative digestion protease LysargiNase, which mirrors trypsin specificity and thus results in C-terminal peptides with N-terminal of Lys and Arg residues [87], appears promising to overcome this challenge [68,88]. Also chemical charge-reversal by derivatization with basic amines such as N,N-dimethylethylenediamine [89] and inclusion of single-charged precursor ions during mass spectrometric analysis improved identification of C-terminal peptides from complex proteomes [69].…”
Section: Challenges In Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, access to terminal peptides in shotgun proteomic studies is still challenging because of the highly dynamic proteome and low abundant terminal peptides . Compared with its counterpart N termini study, protein C termini study is far behind due to two main reasons. , First, reactivity of the carboxyl group is relatively lower than that of the amino group, and it is particularly challenging to achieve site-specific labeling of carboxyl groups in proteins. Second, protein C termini inherently lack basic residues and show low ionization efficiency.…”
mentioning
confidence: 99%